PENGARUH KUALITAS LAYANAN, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUASAN NASABAH KREDIT SERBA BISA PADA PD. BPR BKK KOTA SEMARANG PERIODE JUNI 2019 - Ika Puspita Ardani; Jati Handayani (FInance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2020)
This purpose of this research is to analyze the effect of service quality, product quality, and price on customer satisfaction of Credit Serba Bisa at PD. BPR BKK Kota Semarang Period June 2019. This research is a causal applied quantitative research. The types of data used in this study are primary and secondary. Methods of data collection using questionnaires, interviews, and observation. The sampling technique used was purposive sampling technique with a sample of 100 respondents. Data testing methods used in this study are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression test, F test, t test, test the coefficient of determination R2 which shows can be used to measure customer satisfaction. The analytical method used in this study is multiple linear regression using SPSS 25. The results of the F test show that the quality of service, product quality, and price simultaneously have a significant effect on customer satisfaction on Credit Serba Bisa in PD. BPR BKK Kota Semarang. Furthermore, the t test results showed that service quality, product quality, and price partially had a significant effect on customer satisfaction of Credit Serba Bisa at PD. BPR BKK Kota Semarang.